Assessment of Dentinal Tubules Penetration by Hyben X Delivered into the Root Canal System as an Irrigant; An in Vitro Study - Perez-QuiÃ±ones, Zara; Padilla-Correales, Leonardo; Llanos-Torres, Jose; DÃaz-Caballero, Antonio; Covo-Morales, Eduardo; Taron-Duyoner, Arnulfo (Iranian Endodontic Journal, 2023)
Introduction: Disinfection of the root canal system is crucial for a successful endodontic treatment. Several factors influence the performance of effective irrigation. Diverse irrigating substances have been used but none has proved to completely penetrate the root canal system. HybenX dries biofilm due to its hygroscopic properties; therefore, it is effective in the treatment of biofilm-related diseases. This investigation aimed to estimate HybenX’s degree of penetration into the dentinal tubules of upper first premolars. Materials and Methods: Experimental in vitro intervention where 30 extracted maxillary premolars were evaluated to determine HybenX’s degree of penetration and 5% sodium hypochlorite in the dentinal tubules using three different irrigation techniques (passive ultrasonic irrigation, dynamic manual irrigation and conventional single jet irrigation technique). After preparation, the root canals were irrigated with fluorescent rhodamine 6G; then 500-micrometer sections were made to be analyzed under a fluorescence microscope. Measurements were made in micrometer in ZEN software to determine the penetration degree of each substance in the different root thirds. Results: In the apical third, significant differences between the 3 irrigation techniques were found (P<0.05), similarly, for the middle and cervical thirds. Significant statistical differences between the HybenX and sodium hypochlorite were found at the cervical and middle levels when using the conventional Monoject irrigation and passive ultrasonic irrigation techniques. As for the apical level, differences were found between the passive ultrasonic irrigation techniques and the dynamic manual irrigation technique. Conclusions: Based on this in vitro study, HybenX proved to highly penetrate into the dentinal tubules, especially when using the passive ultrasonic irrigation technique. HybenX may be a useful option for root canal irrigation in endodontics.